2010
DOI: 10.3354/meps08511
|View full text |Cite
|
Sign up to set email alerts
|

Fractal measures of habitat structure: maximum densities of juvenile cod occur at intermediate eelgrass complexity

Abstract: Habitat patchiness is known to alter the relation of a population to both its predators and its prey. We developed a biologically interpretable measure of habitat complexity to test whether juvenile fish density depends on degree of patchiness. In Newfoundland coastal waters, juvenile fish species, including Atlantic cod Gadus morhua, are associated with eelgrass Zostera marina. However, the association of density with eelgrass cover is dependent upon site and the scale of analysis. We tested for non-monotonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 88 publications
(114 reference statements)
2
21
0
1
Order By: Relevance
“…For gadids, we suggest that age 1 represents a transition point in their early life history where individuals become less associated with complex habitat than smaller age 0 cod (e.g. Thistle et al 2010), but exhibit a less defined home range than larger age 2-3 cod (Cote et al 2004). Of our 3 initial potential influences on home range area (season, site of capture, site of release), only season had a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…For gadids, we suggest that age 1 represents a transition point in their early life history where individuals become less associated with complex habitat than smaller age 0 cod (e.g. Thistle et al 2010), but exhibit a less defined home range than larger age 2-3 cod (Cote et al 2004). Of our 3 initial potential influences on home range area (season, site of capture, site of release), only season had a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was also reported by Wilhelmsson et al (2006), who found no correlation between main cold-water fish species, such as the goldsinny, and algae cover but did find a positive correlation between fish occurrence and the availability of suitable habitat features in the form of hiding places. Furthermore, some studies also suggest that some species do not prefer dense stands of submerged aquatic vegetation per se because of a reduced detection distance of approaching predators or a reduced foraging ability (Gorman et al 2009;Thistle et al 2010;Smith et al 2011). Submerged aquatic vegetation areas may therefore serve more as a temporal refuge in case of a real predation risk or to temporally exploit the invertebrate food source (Norderhaug et al 2005) that is often found between structurally complex holdfasts, for example, those of kelp.…”
Section: Discussionmentioning
confidence: 99%
“…Also in a temperate seagrass seascape consisting of patches between 1 and 80 m 2 , predation risk of juvenile cod was best described with a parabolic function, where predation losses were highest at a threshold patch size of 25 m 2 (Gorman et al 2009). Perhaps the most convincing evidence of strong parabolic relationships between fish and seagrass ecosystem configuration is from Newfoundland, Canada, where Thistle et al (2010) found strong parabolic relationships between fish density and eelgrass patchiness across several fish species and spatial scales (Table 3). Furthermore, recent work on the multi-scale relationships between 3-dimensional topographic complexity and fish distributions has detected distinct threshold effects for some coral reef species that exhibit a sensitive dependence for architecturally complex reefs (Pitt man et al 2009).…”
Section: Non-linearities In Animal-habitat Configuration Relationshipsmentioning
confidence: 99%
“…In general, fish and mobile epifauna appear to be robust to even extreme changes in seagrass cover (Pittman et al 2004, Reed & Hovel 2006. Three studies demonstrated a positive parabolic relationship between seagrass patchiness and fish abundance, suggesting that continuous vegetation cover and/or large patches may be suboptimal for many fish species (Salita et al 2003, Gorman et al 2009, Thistle et al 2010. Similarly, nekton populations in salt marshes may benefit from early stages of fragmentation and show positive curvilinear relationships to increasing fragmentation, but populations decline at ~60% (Browder et al 1989) or < 30% marsh cover (Minello & Rozas 2002, Haas et al 2004.…”
Section: Ecological Thresholds In Species-habitat Relationshipsmentioning
confidence: 99%